Ursula Le Guin and Theological Alterity - Anderson, Elizabeth (2016)
The imbrication of politics and religion is becoming a matter of growing interest for young adult writers and readers. Contemporary authors re-deploy the tropes of fantasy writing to craft a mode in which the fantastical is sacred and world creation involves engagement with religious difference and fostering reconciliation. This article focuses on the recent work of Ursula Le Guin to explore recent attention to religious difference in young adult literature: both differences between between people and a more radical alterity between humanity and divinity. Mayra Rivera's postcolonial theology of transcendence, in which God is always beyond human grasp but still implicated in human relations, speaks eloquently to Le Guin's fiction.